Short-term exposure to fine and coarse particles and mortality: A multicity time-series study in East Asia. (December 2015) - Lee, Hyewon; Honda, Yasushi; Hashizume, Masahiro; Guo, Yue Leon; Wu, Chang-Fu; Kan, Haidong; Jung, Kweon; Lim, Youn-Hee; Yi, Seungmuk; Kim, Ho
Abstract: Few studies on size-specific health effects of particulate matter have been conducted in Asia. We examined the association between both fine and coarse particles (PM2.5 and PM10−2.5 ) and mortality across 11 East Asian cities from 4 countries (Korea, Japan, Taiwan, and China). We performed a two-stage analysis: we generated city-specific estimates using a time-series analysis with a generalized additive model (Quasi-Poisson distribution), and estimated the overall effects by conducting a meta-analysis. Each 10−μg/m 3 increase in PM2.5 (lag01) was associated with an increase of 0.38% (95% confidence interval = 0.21%–0.55%) in all causes mortality, 0.96% (0.46%–1.46%) in cardiovascular mortality, and 1% (0.23%–1.78%) in respiratory mortality. Each 10−μg/m 3 increase in PM10−2.5 (lag01) was associated with cardiovascular mortality (0.69%, [0.05%–1.33%]), although this association attenuated after controlling for other pollutants, especially PM2.5 . Increased mortality was associated with increasing PM2.5 and PM10−2.5 concentrations over 11 East Asian cities. Highlights: Few studies on size-specific health effects of PM have been conducted in East Asia. We estimated size-specific PM effects on mortality over 11 East Asian cities. Both fine and coarse particles were associated with mortality in East Asian cites. Effect estimates for fine particles were higher than those for coarse particles. Abstract : Short-term exposure to PM2.5 and PM10−2.5 was associated with an increased risk of mortality in East Asian cities, and PM2.5 effect estimates were higher than PM10−2.5 .